How to get a job in health care - Zedlitz, Robert H., author 559107 (Clifton Park, N.Y. : Delmar, 2013)
Embarking on the health care career of your dreams has never been easier! HOW TO GET A JOB IN HEALTH CARE, 2nd Edition is the ideal reference tool, whether you're a first-time job seeker or a veteran trying to advance in the health care industry. Instruction and preparation activties cover every step of the employment cycle, including job research, writing resumes, completing applications, and preparing for interviews. You will also learn how to start and keep a job in health care, leave a job with grace, and secure references. A great resource for entering any health care profession, this handy guide provides sample documents, templates, worksheets, and activities to help students prepare for their careers. Accompanying software includes a Resume Generator as well as sample and supporting documents related to cover letters, various formats and types of resumes, job offer evaluations, job exit conversations, and much more.